2017
DOI: 10.1164/rccm.201604-0732oc
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Response Mapping as an Imaging Biomarker in Lung Transplant Recipients

Abstract: PRM is a novel imaging tool for lung transplant recipients presenting with spirometric decline. Quantifying underlying small airway obstruction via PRM helps further stratify the risk of death in patients with diverse spirometric decline patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 44 publications
6
48
1
Order By: Relevance
“…In addition, our findings also showed that quantitative CT density analysis can evaluate the difference in survival within the individual diseased groups (RAS and BOS). Previously, similar results were found by Belloli et al using CT images with the PRM technique. Although we did not analyze the expiratory CT as the Belloli group did, we also found that quantitative CT density analysis can be a good imaging biomarker for evaluating CLAD, RAS, and BOS patient survival.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, our findings also showed that quantitative CT density analysis can evaluate the difference in survival within the individual diseased groups (RAS and BOS). Previously, similar results were found by Belloli et al using CT images with the PRM technique. Although we did not analyze the expiratory CT as the Belloli group did, we also found that quantitative CT density analysis can be a good imaging biomarker for evaluating CLAD, RAS, and BOS patient survival.…”
Section: Discussionsupporting
confidence: 86%
“…Change in FEV 1 has been the standard by which BOS is defined despite the fact that it is relatively insensitive to changes in the peripheral airways. There are very few studies that have evaluated different lung function parameters for monitoring allograft function after LTx, with the majority having only adult cohorts . A previous longitudinal study in lung transplanted adults revealed that a concurrent FEV 1 and FVC decline from baseline is associated with fulminant rapid deterioration and a poor prognosis .…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of CLAD remains to be defined; however, the current paradigm is that CLAD results from recipient immune cells or antibodies injuring the allograft airway or alveolar compartments to cause loss of lung function. While new techniques to identify early CLAD with blood or bronchoalveolar lavage biomarkers or imaging, such as parametric response monitoring, 114 are in progress, much work remains to define pathogenesis and optimal treatments. Azithromycin 115,116 and perhaps montelukast 117 appear to be useful adjuncts to maintenance immunosuppression; however, augmenting immunosuppression often leads to infections and the role of steroids and other immunosuppressive agents in the treatment of CLAD is unclear.…”
Section: Complications Of Lung Transplantmentioning
confidence: 99%